Internet addiction: issues and concerns - Ahmed, Helal Uddin (Bangladesh Journal of Medicine, 2023)
There is some addictive use of the internet which ultimately refers to a disorder. Internet addiction is characterized by excessive or poorly controlled preoccupations, urges or behaviors regarding computer use and internet access that led to impairment or distress. The diagnosis “Internet Gaming Disorder” (IGD) has been included in the fifth edition of Diagnostic and Statistical Manual of Mental Disorders. This proposed condition is limited to gaming and does not include problems with general use of the internet, online gambling, or use of social media or smartphones.Co morbidity found in this addictive behavior like depression and anxiety. Treatment options are limited, including Cognitive behavioral therapy, family therapy, couple therapy, antidepressant, anti-anxiety drugs and naltrexone. The mental health professionals, information technologists, young and students affairs professionals should be alert to this disorder. Internet addiction is a growing concern in today’s digital age. With the widespread availability and use of the internet, many people are finding it difficult to control their usage, leading to negative consequences in their daily lives. Some of the issues and concerns related to internet addiction include: Social isolation, Poor academic or work performance, Physical health problems, Sleep disturbances, Risks of Cyber bullying, financial problems, Behavioral and Relationship issues. It is important to seek help if you or someone you know is struggling with internet addiction. Management options may include psychotherapy, support groups, and behavior modification techniques to help individuals regain control of their internet use and improve their overall well-being and sometimes medication need when intractable behavioral issues persist. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 183-184